KARAKTERISTIK PEKERJAAN, KEPEMIMPINAN TRANSFORMASIONAL DAN KINERJA KARYAWAN BANK BPD DAERAH ISTIMEWA YOGYAKARTA CABANG SENOPATI - Nur cahya; Kusmaryati Dwi (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2022)
This study aims to determine the effect of Job characteristic and Transformational Leadership on Employee Performance. The data was collected from all the employees of The Senopati Branch of Bank BPD Daerah Istimewa Yogyakarta as respondents through questionnaire, Likert scale 1-5. The Data was analyzed by Multiple Linear Regression. The Results showed that Job Characteristic and Transformational Leadership influenced Employee Performance positively and significantly.